Understanding technical term translation using language translator as Mobile-Assisted Language Learning (MALL) (ELT Forum: Journal of English Language Teaching, 2022)
Language barriers often prevent a person from understanding information. For that, internet users need to know the best mobile application to translate or translate foreign languages. Numerous mobile apps can be used for English language learning. The apps grow as technology improves then apps were created specifically for the purpose to teach any subject. Mobile-Assisted Language Learning (MALL) is a prominent practice nowadays. The MALL for translation usage is gradually established for EFL students because of the development of ICT. However, the research that discussed this issue is still far on the ground. This research is conducted to fill this void. There are four concerns to consider namely 1) MALL in improving students’ translation skills, 2) Students’ way of translating technical terms 3) The most translation strategy applied by the students to translate the technical terms (4) Challenges faced by students when translating the technical terms from English into Indonesian by using MALL. This research was carried out with a qualitative method. The data were taken from both an online survey and a semi-structured interview. The findings revealed that the students were helpful to use Language Translator (LT) for translating technical terms, especially in determining word choice. They selected three strategies for translating technical terms, i.e. translation by definition, literal translation, and borrowing. The strategy that the students used was a translation by definition. The challenge that they faced when using MALL was primarily regarding guidance availability. Nonetheless, most of them agreed that the LT was very supportive.